KAJIAN FILSAFAT RELASIONALITAS ARMADA RIYANTO ATAS KONSEP TONGKONAN MASYARAKAT TORAJA - Crysan Dwiputra Malla; Robert Pius Manik; Mathias Jebaru Adon (Sanjiwani: Jurnal Filsafat, 2023)
This article discusses Armada Riyanto's relational philosophy in the context of discovering the meaning of the Tongkonan traditional house of the Toraja people. The purpose of this description is to describe the meaning contained in Tongkonan and to reflect on its relevance in the context of living together. The paper is intended as a literature review. The author reviews Armada Riyanto’s book, Relationality, as well as other works about Tongkonan, such as the writings of lecturer, Ivan Sampe Buntu. With this methodology author have the freedom to outline some of the central themes in the book on relationality and its relation to the Tongkonan. This study finally came to the conclusion that every traditional house contains a very rich and deep symbolic meaning. In this symbolic sense, Tongkonan has the power to communicate experiences, justice values and truths in living together.